Analysis of Green Financing and Capital Adequacy on Profitability in the Bank-ing Sector Listed on the Indonesia Stock Exchange (2020-2023) - Panggabean, Michael Armando; Simanjuntak, Arthur; Sagala, Farida (Basic and Applied Accounting Research Journal, 2025)
Green Financing, also referred to as environmentally sound financing, is in line with the long-term development goals set by the United Nations for Environment Protection (UNEP), and involves collaboration with governments, financial authorities, and banking institutions. On the other hand, Capital Adequacy is an important element for banks in building their business and anticipating potential losses. Capital Adequacy Ratio (CAR) is an indicator of a bank's capital that shows management's ability to monitor and control risks that have the potential to affect the bank's capital structure. This study uses a casual associative approach by analyzing the annual reports of each bank, included in the category of quantitative research. The data collection step used is a quantitative method that aims to collect information from the banks that are the object of the research. In this study, there are free and bound variables. A casual associative approach was chosen to observe how much impact Green Financing and Capital Adequacy have on Profitability. Green Financing is used as a variable X1, Capital Adequacy as a variable X2, and Profitability as a variable Y. This research is focused on banking institutions in Indonesia, especially banks that are included in the categories of Book III and Book IV listed on the Indonesia Stock Exchange during the period 2020 to 2023.